Bioactive 4-methoxypyrrolic natural products from two South African marine invertebrates - Rapson, Trevor Douglas (Rhodes University, Faculty of Science, Department of Chemistry, 2005)
This thesis presents an investigation of the 4-methoxypyrrolic constituents of two South African marine invertebrates, the nudibranch Tambja capensis and the bryozoan Bugula dentata. Three known compounds tambjamine A (7), tambjamine E (13) and the tetrapyrrole (15) were isolated during this investigation. All three compounds were shown to be active against oesophageal cancer in accordance with the general anticancer and immunosuppressive properties observed for 4-methoxypyrrolic natural products. Tambjamine A (7), tambjamine E (13) and the tetrapyrrole (15), together with tambjamine K (21) and L (22) (previously isolated in our laboratory) were used as standards to quantitatively assess the presence of these tambjamines in T. capensis and B. dentata collected from three different sites along the South African coast. This study confirmed that B. dentata is the source of the 4-methoxypyrrolic natural products sequestered by T. capensis and eliminated the closely related bryozoan B. neritina as a source of these metabolites. The paucity of tambjamine L (21) and K (22) obtained in previous investigations of the sequestered chemistry of T. capensis prompted an attempt at the development of synthetic methodology that could be used to synthesize tambjamines in sufficient yield for in depth bioactivity studies. In order to by pass the extensively reported problems associated with the synthesis of this group of compound 3-methoxy-2-formylpyrrole (47), readily accessible from 3-methoxypyridine N-oxide (48), was used as the starting material in a singlet oxygen induced 2,2' bipyrrole coupling reaction. Although 47 proved unreactive in this coupling reaction, when the N-Boc protected analogue of 47 was used, and the reaction worked up in the dark, the novel methyl 4-aza-5-oxo-6,6-di-(2-pyrrolyl)-2(Z)-hexenoate (57) was obtained in low yield. The physical properties of tambjamine (E) (13) and the tetrapyrrole (15) were investigated to further the understanding of the proposed oxidative DNA cleavage mechanism and to determine the potential of the 4-methoxypyrrolic natural products as photodynamic therapy agents.
Keywords: Natural products -- South Africa; Marine invertebrates -- South Africa; Bryozoa